1997
DOI: 10.1111/j.1532-5415.1997.tb00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Gait Changes in Older Adults: Predictors of Falls or Indicators of Fear?

Abstract: Changes in gait cited previously as risk factors for falling, i.e., decreased stride length and speed and prolonged double support, may in fact be stabilizing adaptations related to fear of falling. Stride-to-stride variability in the control of gait is an independent predictor of falling and may be a useful measure for identifying high-risk individuals and evaluating preventive interventions. Stride width may also be a useful outcome measure. Contrary to common expectation, a wider stride does not necessarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

72
1,144
18
28

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,432 publications
(1,262 citation statements)
references
References 42 publications
(104 reference statements)
72
1,144
18
28
Order By: Relevance
“…Disparities in testing protocols and disease duration between the samples (mean 13 years), compared to the current study (mean 6 years) may account for these observed differences (Sustakoski, Perera, VanSwearingen, Studenski, & Brach, 2015). Although similar investigations of the relationships between the Walk‐12G and performance‐based gait measures are lacking, fear of falling has been associated with slower gait speeds in healthy older adults (Maki, 1997) and people with PD (Bryant, Rintala, Hou, & Protas, 2014; Rochester et al., 2008). Additionally, Curtze et al.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in testing protocols and disease duration between the samples (mean 13 years), compared to the current study (mean 6 years) may account for these observed differences (Sustakoski, Perera, VanSwearingen, Studenski, & Brach, 2015). Although similar investigations of the relationships between the Walk‐12G and performance‐based gait measures are lacking, fear of falling has been associated with slower gait speeds in healthy older adults (Maki, 1997) and people with PD (Bryant, Rintala, Hou, & Protas, 2014; Rochester et al., 2008). Additionally, Curtze et al.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the generated time series of stride time (and/or swing time or other parameters) can then become the input to algorithms that quantify the dynamics. For example, stride time variability, the magnitude of the stride-to-stride fluctuations in the gait cycle duration, is calculated by determining the standard deviation (SD) or the coefficient of variation (CV) of each subject's stride time time series (Maki, 1997;Hausdorff, Edelberg et al, 1997;Hausdorff, Rios et al, 2001). Similar methods can be used to study the variability of other measures of gait timing (e.g., swing time).…”
Section: Notes On Nomenclature and Data Collection Methodsmentioning
confidence: 99%
“…Although many gait parameters might appear to be useful for distinguishing between fallers and non-fallers, studies suggest that this is not actually the case; rather, features often associated with fallers more closely reflect fear of falling and a cautious gait (Feltner, MacRae, & McNittGray, 1994;Hausdorff, Edelberg et al, 1997;Hausdorff, Rios et al, 2001;Maki, 1997). Building on the suggestions of Gabell and Nayak (1984), we hypothesized that quantitative measures of gait unsteadiness, as reflected in the temporal parameters of gait, might be increased in elderly fallers.…”
Section: Quantifying Fall Risk and Gait Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In knee osteoarthritis, reduced variability of knee movements has been reported (Fallah-Yakhdani et al, 2010;Lewek et al, 2006). Reduced variability may be harmful to the joint (Lewek et al, 2006), but increased variability suggests a lack of control, and coincides with a higher risk of falling (e.g., Hausdorff, 2007;Leitner et al, 2007;Maki, 1997). Earlier, we hypothesised that subjects with knee osteoarthritis co-contract in order to reduce variability (Fallah-Yakhdani et al, 2010), which may enhance the control over knee motion (e.g., Benedetti et al, 2003;Kean et al, 2009;Schmitt and Rudolph, 2008;Van Dieën et al, 2003).…”
Section: Introductionmentioning
confidence: 99%